ECE551: Multimedia Systems and Applications / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
This course provides students with the essential knowledge on multimedia systems and applications. To develop knowledge and understanding of the underlying hardware and software developments which enable multimedia technology developments.